Hybridization State Detection of DNA-Functionalized Gold Nanoparticles Using Hyperspectral Imaging - Richard C. Murdock; Omar A. Khan; Thomas J. Lamkin; Saber M. Hussain; Nancy Kelley-Loughnane (International Journal of Optics)
Hyperspectral imaging has the unique ability of capturing spectral data for multiple wavelengths at each pixel in an image. This gives the ability to distinguish, with certainty, different nanomaterials and/or distinguish nanomaterials from biological materials. In this study, 4 nm and 13 nm gold nanoparticles (Au NPs) were synthesized, functionalized with complimentary oligonucleotides, and hybridized to form large networks of NPs. Scattering spectra were collected from each sample (unfunctionalized, functionalized, and hybridized) and evaluated. The spectra showed unique peaks for each size of Au NP sample and also exhibited narrowing and intensifying of the spectra as the NPs were functionalized and then subsequently hybridized. These spectra are different from normal aggregation effects where the LSPR and reflected spectrum broaden and are red-shifted. Rather, this appears to be dependent on the ability to control the interparticle distance through oligonucleotide length, which is also investigated through the incorporation of a poly-A spacer. Also, hybridized Au NPs were exposed to cells with no adverse effects and retained their unique spectral signatures. With the ability to distinguish between hybridization states at nearly individual NP levels, this could provide a new method of tracking the intracellular actions of nanomaterials as well as extracellular biosensing applications.